1070 A Systematic Review of Seymour Fracture Management. (12th October 2021) - Khanal, P; Srivastava, A; Zargaran, D; Zargaran, A; Nikkhah, D; Mosahebi, A
Abstract: Aim: Seymour fractures are distal phalanx fractures of the finger in children with a juxta-epiphyseal or Salter-Harris Type I/II pattern associated with a nail-bed injury. There remains a paucity in literature regarding the development of complications between Seymour fracture management options, with early studies encouraging non-operative management due to the increased rates of post-operative infection. This systematic review aims to identify present-day, optimal management strategies for Seymour fractures, with further analysis of infection rates and secondary outcomes during post-operative recovery. Method: Free-text search, MeSH terms and expanded keywords/phrases were employed to search the PubMed, Embase (via Ovid), Web of Science and CINAHL databases. Studies that described the management of Seymour fractures in paediatric patients were included, subject to inclusion/exclusion criteria. The data extracted included the sample size, intervention, infection rates and secondary outcomes. Results: An initial search identified 305 articles, following the PRISMA guidance, 8 studies were eligible for full-text analysis. Across all studies, 307 Seymour fractures were identified (mean age, 10±1.2 years). A cross-study analysis showed a lower rate of adverse outcomes (including malunion/non-union and unplanned operative intervention) for K-wire fixation when compared to external splinting, 8.3% and 20.7% (P ≤ 0.001), respectively. Conclusions: There was no statistically significant difference between non-operative and operative management in rates of infection and adverse outcomes. However, further analysis revealed a significantly lower risk of complications in patients who received K-wire fixation when compared to external splinting. Nonetheless, further studies with greater levels of evidence need to be carried out to consolidate this.